Differences in goal scoring and minutes of scoring between two European championships, one among 16 teams (EURO 2012) and the other among 24 teams (EURO 2016) - Tousios, T.; Michailidis, Y.; Mandroukas, A.; Mikikis, D.; Metaxas, T. (Facta Universitatis: Series Physical Education and Sport, 2018)
The purpose of this study was to record and compare the goal scoring patterns and the minutes of the game that goals were scored between two Euro Cups (2012 and 2016). All matches (n=82) of both the Euro Cups were video taped and analyzed using the sport software Sportscout. Chi-square methods were used for the data analysis and the level of significance was set at p<0.05. The team that scored the first goal in a match was the winner of that match 70.97% of the time in Euro 2012 and 72% in Euro 2016. In open play, the highs of all the actions were more frequent prior to a goal which involved a cross or a through pass. The 15-min analysis showed that the most goals (20%) were scored between the 46th-60th min of the game in the Euro Cup 2012. Furthermore, in the Euro Cup 2016 the most goals were scored between the 31st-45th minute (19%), 46th-60th minute (19%) and between the 76th-90th minute (18%). No differences between the Euro Cups observed. The results indicated that coaches have to make sure their teams score first, press in the offensive third and prepare their players well in set plays to be more effective.